DESAIN PENGEMBANGAN POTENSI “EKOWISATA KAWASAN PASAR IKAN DESA KEDUNGOMBO BATURETNO” - Iwan Ristanto; Satria Agung Wibawa (Inisiasi, 2022)
RPJMDes Kedungombo 2019-2025, APBDes 2021 Fish Market Development Plan, Village financial policy directions and regional priority programs, accompanied by work plans including "Development of Fish Market Area Potential". For this reason, comprehensive planning is needed from the aspect of developing village areas through a Master Plan which will be assisted by the service staff in this case the Civil Engineering Study Program Service Team, Universitas Veteran Bangun Nusantara Sukoharjo."PKM Potential Development "Ecotourism in the Fish Market Area of ​​Kedungombo Village" Service activities through planning and developing village potential are carried out through several stages, as follows:(1) Licensing and Cooperation in Kedungombo Village, Baturetno,(2) Survey and Measurement,(3) Pre-Design Creation and Presentation,(4) Design Public Outreach & Test, (5) Revision of Design Drawings and Calculation of RAB. The development of the Fishing Pond Area and Selfie Area in Kedungombo Village, Baturetno, there was an increase in understanding of 67%, while 2) Participants' understanding of the Bestek (Development Plan) and RAB images increased by 75% from a total of 26 (twenty six) participants representing the community. attended the socialization and public test of the Ecotourism Development Design for Fish Market Area in Kedungombo Village, Baturetno.